Many-dimensional Dirichlet and Tricomi problems for one class of hyperbolic-elliptic equations - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For the generalized many-dimensional Lavrent’ev-Bitsadze equation, we prove the unique solvability of the Dirichlet and Tricomi problems. We also establish the existence and uniqueness of a solution of the Dirichlet problem in the hyperbolic part of a mixed domain.